Trial, error and economic development in colonial Punjab: The Agri-Horticultural Society, the state and sericulture experiments, c. 1840–70. (January 2015) - Lally, Jagjeet
The history of economic change in colonial and post-colonial Punjab is well-studied, at least for the period from c. 1880, when Punjab became a major producer of relatively low-value-added crops, such as cereals, raw cotton and sugar. This article argues that the colonial state's intervention in the economy in the 1840s to 1870s—the decades of the British colonial conquest of Punjab and the early administration in the province—should not be seen as a prelude to later developments. Specifically, this article argues that state policy proceeded by trial and error, that the state worked through a seemingly private organisation—the Agri-Horticultural Society—to trial a scheme that sought to re-model Punjab as a producer of higher-value-added commodities for the global market such as silk following the precedent of colonial Bengal, and that the resultant failure of these experiments contributed to the changes in policy and the pattern of development from the final-quarter of the century. In studying the Agri-Horticultural Society's silk experiments, furthermore, this article also sheds light on the history of the early colonial state and the history of sericulture in Punjab.